Decomposition Behavior of Triarrhena lutarioriparia Tissues in Dongting Lake Water: A Laboratory Simulation Study. Issue 3 (3rd February 2022) - Zhao, Yuanyuan; Xu, Youze; Fu, Guangyi; Tang, Nan; Zhou, Shuang
Abstract: Following the overall withdrawal of papermaking enterprises, Triarrhena lutarioriparia, a most abundant macrophyte of Dongting Lake wetland, will remain to be uncut and decay in the lake water. The decomposition dynamics of T. lutarioriparia tissues and the decomposition effects on water quality are investigated in this study. The results show that two main processes are observed during the 90‐day decomposition period of T. lutarioriparia : rapid leaching and gradual biodegradation. During the initial 10‐day leaching process, the initial weight loss of leaves, spikes, and stems reached 13.33%, 12.44%, and 4.67%, respectively; meanwhile, 15.12–32.62% of total nitrogen and 24.16–45.45% of total phosphorus in the tissues are released to the water. The decomposition rate of T. lutarioriparia tissues is in the order: spikes (0.0053 day −1 ) > leaves (0.0045 day −1 ) > stems (0.0033 day −1 ). The T. lutarioriparia decomposition exerted adverse effects on the lake water quality, including the depletion of dissolved oxygen, the increase in concentrations of organic matter and nutrients, especially during the rapid leaching process. Such adverse effects are significantly associated with both the biomass (p < 0.001) and the species of T. lutarioriparia tissues (p < 0.05). Abstract : Following the overall withdrawal of papermaking, large‐scale Triarrhena lutarioriparia tissues will decay in the Dongting Lake water. The decomposition rate of T. lutarioriparia spikes (0.0053 day −1 ) is higher compared to leaves (0.0045 day −1 ) and stems (0.0033 day −1 ). The uncut T. lutarioriparia can cause a substantial increase of nutrients concentration in lake water within short term.